Effect of doping on the magnetic ordering of quasi-one-dimensional antiferromagnets - Zvyagin, A.A. (Физика низких температур, 2006)
We have studied theoretically how nonmagnetic dopants, which change the local coupling of
spins to the host, affect the low-temperature thermodynamic characteristics of quasi-one-dimensional
(Q1D) quantum spin antiferromagnets. Our theory qualitatively and, in some cases, quantitatively
describe the behavior of the magnetic susceptibility and specific heat of the Q1D system
BaCu₂(Si₁₋xGex)₂O₇. We have shown that in some cases the strong disorder in the distribution of
characteristics of magnetic impurities in quantum antiferromagnetic spin chains can be the cause of
magnetic ordering, if such chains are weakly coupled to each other, while for homogeneous chains
and chains with a weak disorder a small enough coupling between chains does not produce magnetic
ordering. For other values of the parameters, magnetic impurities can decrease the Neel temperature
compared to that of the homogeneous Q1D spin system.